186k views
1 vote
What should you multiply the first equation (top equation) by in order to eliminate the variable y when the two equations are added together? {x+2y=5{3x-4y=8

1 Answer

7 votes

2

Step-by-step explanation

given


\begin{gathered} x+2y\rightarrow equation(1) \\ 3x-4y=8\rightarrow equation(2) \end{gathered}

Step 1

a) to eliminate the y variable we have


\begin{gathered} 2y \\ -4y \end{gathered}

in order to be eliminated both terms must have the same value and different sign,in other words the addition must equla zero, so weed a number (a) that makes the term from teh first equation equals (4y)

so


\begin{gathered} (2y*a)-4y=0 \\ 2ay=4y \\ so \\ 2a=4 \\ divide\text{ both sides by 2} \\ (2a)/(2)=(4)/(2) \\ a=2 \end{gathered}

therefore, the first equation should be multiplied by 2

I hope this helps you

User Bopha
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.